A narrative review on inhibitory effects of edible mushrooms against malaria and tuberculosis-the world’s deadliest diseases - Ashaimaa Y. Moussa; Baojun Xu (Food Science and Human Wellness)
The isolated secondary metabolites from 39 edible mushrooms are reported, among which 107 compounds were active, 61 demonstrated antitubercular activities with IC50 range of 0.2–50 µg/mL and 46 manifested antimalarial effects with IC50 range of 0.061–36 µg/mL. While more than 2000 strains of edible mushrooms are identified, this review shows the paucity of research in these rich organisms featuring a vital culinary ingredient worldwide. A thorough search was conducted on basidiomycetes to discuss the chemistry and biology of the isolated compounds, structure activity relationships (SAR) as well as the cytotoxicity profiles of, primarily, the active anti-plasmodial and antitubercular molecules. With a safe cellular profile, lanostane triterpenoids were found to be the only molecules with combined activities against both diseases. SAR correlations reviewed here indicated the significance of 3β- and 7α-hydroxylation in the anti-tuberculosis activity and the terminal unsaturated moiety between C-4 and C-28 in the antimalarial activity in the same terpene skeleton. This review will attract the attention of medicinal chemists, and food scientists to optimize and rationalize the use of mushrooms both as unexploited sources of novel molecules and as nutraceuticals to treat two of the deadliest infectious diseases, malaria, and tuberculosis.